ASP.NET for Web designers - Ladka, Peter (Voices Ser., 2002)
Teaching ASP.NET in a non-linear format that creative thinkers can easily grasp and understand without the typical programming jargon. Provides clear and concise, hands-on, real-world examples right from the beginning of the book. The book contains a natural progression by providing foundational information in the opening chapters. Content will be presented with "hands-on" examples so the opening chapters will also be laying the groundwork for more advanced subjects by not only presenting the information but by writing code as well. The middle section of the book covers the key cast members on the .NET stage including HTML Controls, Web Controls and List Controls. The third and final section of the book covers more advanced issues in ASP.NET including data access and security issues.